2018
DOI: 10.1155/2018/6754030
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Surgical Dissection for Penile Transplantation for Trans-Men: A Cadaveric Study

Abstract: Introduction The surgical techniques currently available for penile reconstruction for trans-men with gender dysphoria present with multiple drawbacks and often fail to meet patients' expectations. Literature reports three cases where penile transplantation has been performed for cis-men, with the last two cases being considered successful. Aim To determine whether an en bloc surgical dissection can be performed in a male cadaver, in order to include structures necessary for penile transplantation (from a dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Though preliminary results have been promising, longer-term studies are needed to determine the comparative utility of this device. Finally, with cadaveric penile transplantation emerging as an option for patients with genital loss, this may conceivably serve as a future option for transgender men (46,47). With greater recognition of the needs of transgender patients, we are hopeful that further developments of trans-specific devices are on the horizon.…”
Section: Future Directionsmentioning
confidence: 99%
“…Though preliminary results have been promising, longer-term studies are needed to determine the comparative utility of this device. Finally, with cadaveric penile transplantation emerging as an option for patients with genital loss, this may conceivably serve as a future option for transgender men (46,47). With greater recognition of the needs of transgender patients, we are hopeful that further developments of trans-specific devices are on the horizon.…”
Section: Future Directionsmentioning
confidence: 99%
“…The repair of injured corpora cavernosa has always been difficult due to a variety of anatomical, aesthetic, and functional challenges 2 . Allopenis transplantation, a reported approach, is controversial because of ethical issues 3,4 . Acellular matrix replacement also has defects because of limited sources, potential immunogenicity, and low porosity and fails to restore penile function 5 .…”
mentioning
confidence: 99%
“…Surprisingly, angiogenesis induced by the expression of the HIF-1α and VEGF (via HIF-1α mutated MDSCs) in the hydrogel scaffolds effectively repaired the injured corpora cavernosa, and restored penile erection and ejaculation function in vivo within 4 months ( Fig. 1), in sharp contrast to unsuccessful repair by the aforementioned traditional repairing methods [3][4][5] . Specifically, the angiogenic factors generated by HIF-1α over-expressed MDSCs were enriched on the surface of 3D-printed hydrogel scaffolds by the adsorption of heparin and then stimulated blood vessel formation in vivo.…”
mentioning
confidence: 99%
“…Selvaggi et al have shown that it is possible to explant the penis and associated vessels, nerves, and urethra en bloc from a cadaver. 20 These authors concluded that this technique would enable penile transplantation from a cadaveric donor male to a recipient with natal female pelvic anatomy, a finding that has been previously confirmed by Tiftikcioglu et al 21 …”
Section: Introductionmentioning
confidence: 69%